Knowledge, attitudes, and practices of emergency department staff towards disaster and emergency preparedness at tertiary health care hospital in central Saudi Arabia - Nofal, Abdullah (Saudi Med J, 2018)
OBJECTIVES: To assess the knowledge, practices, and attitudes regarding disaster and emergency preparedness among Emergency Department (ED) staff. METHODS: This cross-sectional study was conducted at Tertiary health care hospital in central Riyadh, Kingdom of Saudi Arabia. A self-administered survey was utilized to collect data from ED physicians and nurses. The questionnaire was divided into 5 sections viz; demographics, knowledge about disaster management and preparedness, attitudes about disaster planning, current role and practices, and familiarity towards emergency. RESULTS: A 189 participants have completed the questionnaire. Two-third of the participants were below 30 years, and more than 85% were female. One hundred and eleven (58.7%) had a clinical experience of more than 5 years, while 78 (41.3%) participants had more than 3 years of clinical service at the Tertiary care hospital in Riyadh, Kingdom of Saudi Arabia. Correct responses of knowledge towards disaster and emergency preparedness score was 6.2±2.5. Participants with more than 5-years of experience had a statistically significant (p=0.009) knowledge scale score for disaster and emergency preparedness. Overall, 186 (98.4%) patients believed that training is necessary for all healthcare workers. Approximately 153 (81%) participants reported the conduct of disaster drill at their hospital. The mean score (Mean±SD) for the overall familiarity of the study participants with emergency preparedness information questionnaire (EPIQ) scale was 3.2±1.3. CONCLUSION: The level of knowledge was satisfactory among healthcare providers with neutral level of attitude, practice, and familiarity regarding disaster preparedness. Follow-up research is necessary for maximizing ED preparedness.